Vloga tunelskih nanocevk v medceličnem sporazumevanju in (pato)fiziologiji - Resnik, Nataša (Medicinski razgledi, 2024)
Intercellular communication is a vital process that enables normal tissue development, cell renewal, and survival. The recently discovered tunneling nanotubes are one of the types of intercellular communication. They are thin tubular membrane-cytoplasmic protrusions that connect different cell types in vitro and in vivo. Tunneling nanotubes act as communication tunnels by allowing the transport of cellular cargo such as cell organelles, lipids, proteins, nucleic acids, as well as non-cellular material such as pathogens and nanoparticles from the donor cell to the target cell. When a deleterious cargo (damaged organelles, oncoproteins, and pathogens) is transferred, tunneling nanotubes play a pathophysiological role by participating in both the onset of disease and its spread. Tunneling nanotubes are thus highly heterogeneous in terms of function, and this is likely also the origin of their structural heterogeneity. Tunneling nanotubes of different cell types differ in length, diameter, formation, and composition of cytoskeletal elements. Understanding the structure and function of tunneling nanotubes is critical to understanding disease and treatment options. This review describes the mechanisms of formation and the role of tunneling nanotubes known to date and presents some of the latest findings on the use of tunneling nanotubes for therapeutic purposes.
Keywords: citoskeletni elementi; kokultura; medcelično sporazumevanje; onkoproteini; tarčno zdravljenje; tunelske nanocevke; urotelijske celice